Pengembangan Prototipe SmartEdu: Pembelajaran Berbasis Kuis Interaktif untuk Menguji Pemahaman Siswa Sekolah Dasar terhadap Materi Pembelajaran - Maura Y’nauri Yasmin Hidayat; Devy Dwi Arianty; Izzatu Salisah Mafatihurrohmah; Hikam Muta’aly Al-Isyraq Panto; Aufa Zaskiah Rahma’ Aini; Aditya Pamungkas Yohanlis; Syifa Aulia; Michelle Aprilyn Hartanu (Indo Publishing, 2026)
Learning media plays a crucial role in helping teachers deliver material effectively, particularly at the elementary school level, which demands an active, enjoyable learning environment that is appropriate to students' developmental stages. However, many elementary schools still employ conventional learning methods that rely on lectures and simple media, leading to student boredom and a lack of motivation. This study aims to develop SmartEdu Games as a prototype for educational game-based learning media designed to increase student interest and engagement in thematic learning. The study employed the Research and Development (R&D) method with the ASSURE design model, but was only implemented up to the prototype development stage because the study did not involve expert validation or student trials. The prototype product was designed to include learning materials, interactive activities, and mini-games as practice tools. The results of the study indicate that SmartEdu Games was successfully developed as an initial prototype that has the potential to be used as an interactive learning medium at the elementary school level. This prototype can be an alternative digital media that supports independent learning and teacher mentoring, and has the potential for further development in the validation and trial stages